Intermediates in V(D)J recombination: A stable RAG1/2 complex sequesters cleaved RSS ends - Jones, Jessica M. (The National Academy of Sciences, 2001)
Rearrangement of gene segments to generate antigen receptor coding regions depends on the RAG1/2 recombinase, which assembles a synaptic complex between two DNA signal sequences and then cleaves the DNA directly adjacent to the paired signals. After coupled cleavage of complementary signal sequences, virtually all of the cleaved signal ends remained associated with RAG1/2 in stable complexes. These signal end complexes were distinct from various precleavage RAG1/2 signal complexes in that they were resistant to treatment with heparin. A mammalian joining apparatus consisting of purified Ku70/86, XRCC4, and DNA ligase IV proteins was sufficient to join deproteinized cleaved ends, but retention of signal sequences within the signal end complex blocked access to the DNA ends and prevented their joining by these proteins. Sequestration of cleaved ends within the signal end complex would account for the persistence of these ends in the cell after cleavage and may explain why they do not normally activate the DNA-damage-dependent cell cycle checkpoint.